Female labor Force Participation in an Era of Organizational and Technological Change - Marina Adshade (Queen's University, Department of Economics, 2007)
This paper examines the endogenous interaction between the rise in female labor force participation and changes in both the method and mode of production that occurred during the early part of the 20th century. Within a dynamic general equilibrium framework, an exogenous expansion in the skill level of the population induces an organizational change at the firm level and a redirection of investment towards new technologies that complement the skills of the emerging workforce. In addition to allowing for a change in the method of production in a market with directed technical change, a framework is developed to explicitly examine the transitional dynamics as skilled workers become relatively abundant. The rise in the skill level explains the rise in female labor force participation, the increase in women's wages and the decline of the clerical wage relative to manufacturing.
Keywords: O14; E23; N12; 330; female labor force participation; clerical work; organizational change; technological change; Organisatorischer Wandel; Technischer Fortschritt; Weibliche Arbeitskräfte; Büroberufe; Qualifikation; USA